2014
DOI: 10.1186/1756-0500-7-265
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal interventions to reduce preterm birth: an overview of Cochrane systematic reviews

Abstract: BackgroundSeveral factors are associated with an increased risk of preterm birth (PTB); therefore, various interventions might have the potential to influence it. Due to the large number of interventions that address PTB, the objective of this overview is to summarise evidence from Cochrane reviews regarding the effects and safety of these different interventions.MethodsWe conducted a systematic literature search in the Cochrane Database of Systematic Reviews. Included reviews should be based on randomised con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
3
20
0
2
Order By: Relevance
“…43 A previous overview review focused on antenatal interventions to prevent PTB. 15 Our results are consistent with this review with two exceptions. Piso et al found that vitamin C supplementation during pregnancy increased the risk of PTB and magnesium supplementation decreased the risk of PTB, LBW and SGA.…”
Section: Preventive Antimalarial Drugssupporting
confidence: 93%
See 1 more Smart Citation
“…43 A previous overview review focused on antenatal interventions to prevent PTB. 15 Our results are consistent with this review with two exceptions. Piso et al found that vitamin C supplementation during pregnancy increased the risk of PTB and magnesium supplementation decreased the risk of PTB, LBW and SGA.…”
Section: Preventive Antimalarial Drugssupporting
confidence: 93%
“…As antenatal interventions to reduce PTB were recently reviewed, we did not include reviews that focused only on PTB. 15 Nutrition-specific and nutrition-sensitive interventions periconceptionally and/or during pregnancy were considered for inclusion. We included reviews where participants were women with a singleton pregnancy despite any potential risk of LBW.…”
Section: Methods Search Strategy and Selection Criteriamentioning
confidence: 99%
“…There seems to be an upward trend [2,3], which contributes to almost 3.6 million preterm births accounting for 23.6% of the global preterm births reported each year [4]. Preterm birth has been consistently associated with maternal underweight and nutrient deficiencies during pregnancy [5][6][7][8][9].…”
mentioning
confidence: 99%
“…7 Bir baş-kasında, 20-37. haftalar arasında doğum ağrılarının hissedilmesi, kontraksiyonların saptanması (4/20 dk veya 6/60 dk), membran rüptürü veya >20 mm servikal açıklık, %80'in üzerinde servikal silinme veya membranların intakt olmakla birlikte süreç içinde servikal açılma veya silinmenin artması kriterler arasındadır. 8 Preterm eylem tehdidi, servikal değişikliklerin eşlik etmediği kontraksiyonların saptanması durumudur. 9 Servikal uzunluk ölçümü için en güvenilir yöntem, TVUSG'dir.…”
Section: Tanimunclassified